The Pro12Ala polymorphism of PPARγ2 modulates beta cell function and failure to oral glucose‐lowering drugs in patients with type 2 diabetes. Issue 3 (2nd September 2020) - Masulli, Maria; Della Pepa, Giuseppe; Cocozza, Sara; Capasso, Mario; Pignataro, Piero; Vitale, Marilena; Gastaldelli, Amalia; Russo, Marco; Dolce, Pasquale; Riccardi, Gabriele; Rivellese, Angela A.; Vaccaro, Olga
Abstract: Background: We evaluate whether the Pro12Ala polymorphism of peroxisome proliferator‐activated receptor γ2 (PPARγ2) has a role in the progression of diabetes by modulating the occurrence of treatment failure to glucose‐lowering drugs. Methods: We studied 215 patients with type 2 diabetes participating in the Thiazolidinediones Or Sulphonylureas and Cardiovascular Accidents Intervention Trial study. All participants were insufficiently controlled (glycated haemoglobin [HbA1c ] 7.0%‐9.0%) with metformin 2 g/day and were randomly allocated to add‐on pioglitazone or a sulfonylurea. Treatment failure was defined as HbA1c ≥8% on two consecutive visits, 3 months apart. Results: Carriers or non‐carriers of the polymorphism had similar age, body mass index, and diabetes duration. Ala carriers had lower fasting plasma insulin, better insulin sensitivity (Homeostasis Model Assessment [HOMA]2‐%S), and worse beta cell secretion (HOMA2‐%B) than non‐carriers. During 24 months of follow‐up, 32.5% among the Ala carriers and 8.6% among non‐carriers ( P  < 0.001) developed treatment failure with a cumulative incidence of 18.6 vs 4.6/100 person‐years. Those patients who developed treatment failure were older, had a younger age at diabetes diagnosis (48 ± 10 vs 52 ± 7 years; P = 0.032), higher HbA1c (8.1 ± 0.5 vs 7.7 ± 0.5%; P  < 0.001), and lower HOMA2‐%B (30 ± 12 vs 46 ± 29; P = 0.015) at study entry, as compared to those who did not develop treatment failure. At multivariate analysis, the Pro12Ala polymorphism was significantly associated with treatment failure (hazard ratio [HR] 4.45; 95% confidence interval [CI] 1.79‐11.1; P  < 0.001); HbA1c at study entry was the other independent predictor of failure in this study population. Conclusion: The Pro12Ala polymorphism is associated with a greater insulin sensitivity, reduced beta cell function and a substantially increased risk of treatment failure.